Faktor-Faktor yang Mempengaruhi Tingkat Pengangguran di Provinsi Jawa Barat pada Tahun 2018-2023 - Rizka Elfina Aulia; Shavera Sofiana Malia; Amin Pujiati; Dyah Maya Nihayah (Universitas Nusantara PGRI Kediri, 2024)
Unemployment has an impact on countries that are experiencing economic growth, especially developing countries like Indonesia, it needs to be discussed in the context of this unemployment problem. In this research, the aim is to determine the impact of HDI, education level, and economic growth on the unemployment rate in West Java province from 2018 to 2023. Quantitative techniques and secondary data methods were used to complete this research with the guidance of 2018–2023. Time series data from the West Java Central Statistics Agency from 2018–2023 was used in completing this research. After the analysis test was completed, the research results were as follows: economic growth, education level, and HDI simultaneously influenced unemployment in West Java Province from 2018 to 2023 significantly; Partial economic growth does not affect unemployment in West Java Province from 2018 to 2023. Education level also influences unemployment in West Java Province from 2018 to 2023. It is hoped that the government will consider this carefully, considering that economic growth plays an important role in reducing unemployment.